‘Some men deeply hate women, and express that hatred freely': Examining victims' experiences and perceptions of gendered hate crime - Mason-Bish, Hannah (International review of victimology, 2020)
Extensive debate about the place of gender within the hate-crime policy domain has been fuelled by national victimisation surveys indicating people's experiences of ‘gender hate crime' coupled with Nottinghamshire Police's decision to begin categorising misogynistic street harassment as a form of hate crime. Drawing on the results of an online survey of 85 respondents, this article explores people's experiences of gender-related victimisation as ‘hate crimes'. The analysis demonstrates how participants relate their experiences to the concept of hate crime, their perceptions on punishment and reporting to the police, and also wider impacts on their recovery processes. This paper provides a timely contribution towards current debates around using the existing hate-crime model for addressing crimes motivated by gender hostility.